The whale scientists : solving the mystery of whale strandings - Hodgkins, Fran, 1964- (Boston : Houghton Mifflin Co., 2007)
Discusses the history of whales and how scientists are trying to find out why there are whale strandings.
Includes bibliographical references (p. 54-56) and index.
Keywords: Whales -- Juvenile literature; Whaling -- Juvenile literature; Whales -- Stranding -- Juvenile literature